Farsa panny Heni ; Czarny Bog - Rodziewiczowna, Maria, 1863-1944.; Rodziewiczowna, Maria, 1863-1944. (Warszawa : "Alfa", 1991)
Two tales about arranged marriages in the last quarter of the 19th century.
Keywords: Marriage customs and rites -- Slavic countries -- Fiction